1990
DOI: 10.1002/1097-4679(199011)46:6<782::aid-jclp2270460614>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

A limitation of using the wiener and harmon obvious and subtle scales to detect faking on the MMPI

Abstract: More frequent endorsement of obvious than subtle items on the MMPI has been advocated as a strategy to detect negative response bias. An assumption of this strategy is that faking is correlated differentially with obvious and subtle items, whereas psychopathology is not. In order to evaluate this assumption, MMPI profiles were obtained from the records of 375 psychiatric inpatients. Analysis revealed a strong positive correlation between profile elevation and obvious minus subtle differences. Excluding MMPIs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

1992
1992
1996
1996

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…In another review, Schretlen (1988) reported similar findings. Schretlen (1990) also reported high correlations between the Obvious item scores and MMPI profile elevation. Schretlen concluded that “large O-S differences actually should be expected in highly elevated MMPI profiles obtained from psychiatric inpatients…even when other MMPI indices suggest that a profile is valid” (p. 785).…”
mentioning
confidence: 92%
“…In another review, Schretlen (1988) reported similar findings. Schretlen (1990) also reported high correlations between the Obvious item scores and MMPI profile elevation. Schretlen concluded that “large O-S differences actually should be expected in highly elevated MMPI profiles obtained from psychiatric inpatients…even when other MMPI indices suggest that a profile is valid” (p. 785).…”
mentioning
confidence: 92%
“…The clinical use of the Wiener and Harmon (Wiener, 1948) Subtle and Obvious scales has had a long and controversial history. Originally developed to detect deviant test-taking attitudes in the MMPI, the clinical utility of the Subtle and Obvious scales is questionable, as research that used the original MMPI clearly has shown (Dannenbaum & Lanyon, 1993;Herkov, Archer, & Gordon, 1991;Peterson, Clark, & Bennett, 1989;Rogers, 1983;Schretlen, 1988Schretlen, , 1990Wrobel & Lachar, 1982) and MMPI-2 (Berry, Baer, & Harris, 1991;Boone, 1994a;Butcher, 1989;Graham, Watts, & Timbrook, 1991;Herkov, Gordon, Gynther, & Greer, 1994;Peterson et al, 1989;Timbrook, Graham, & Watts, 1993;Weed, Ben-Porath, & Butcher, 1990). To summarize, the Subtle and Obvious scales "have led to ambiguous identification of faking" (Dubinsky, Gamble, & Rogers, 1985, p. 67) and may "attenuate the validity of the Full Scale by introducing variance that is not related to variance in the criterion measure" (Weed et al, 1990, p. 12).…”
mentioning
confidence: 99%
“…In fact, the subtle items may actually lower the validity of the full-scale score (Weed, BenPorath, & Butcher, 1990). Schretlen (1990) likewise found a high false-positive rate for malingering using the Subtle and Obvious scales. Wetter et al (1992) also suggest further development of the Ds 2 scale, the MMPI-2 items remaining from the MMPI Dissimulation Scale, when used in combination with other scales, such as, VRIN.…”
Section: Malingering and Defensiveness In Mtbl Zlellnsklmentioning
confidence: 91%